Ethnomedicinal uses of plants for blood purification in disitrict Swabi, Khyber Pakhtunkhwa, Pakistan - Rozina,; Ahmad, Mushtaq; Zafar, Muhammad; Zainulabidin, Sheikh; Qasim, Muhammad (Journal of Pure and Applied Agriculture, 2023)
The present study represents the first ethnobotanical study to record the indigenous knowledge of district Swabi about the use of sixty-six medicinal plants for blood purification. ABSTRACT Medicinal plants act as a very important and accessible source of blood purification in the rural communities of district Swabi, Pakistan. Current study represents the first ethnobotanical study of district Swabi to keep the record of medicinal plants to be used as blood purification. Approximately, 190 informants including local people (88.95%) and local health practitioners (LHPs) (11.5%) were interviewed for ethnomedicinal data documentations using semi structured interviews. Quantitative ethno botanical indices like frequency citation (FC), relative frequency citation and family importance value (FIV) were used to analyze the data. Total 66 medicinal plants belonging to 41 families and 63 different genera have been reported as blood purifying plants. Results indicated that Zygophyllaceae, Asteraceae and Solanaceae are families with more number of species (each have 4 sub-species), herbs were documented as dominant life form (71%). Relative frequency citation value ranges from 0.11- 0.95 in the current study. Azadirachta indica A. Juss., Fumaria indica (Hausskn.) Pugsley, Cuscuta reflexa Roxb, Mimosa pudica Mill. and Melia azedarach are the mostly cited blood purifying plant species. Approximately 50 plant species were reported as blood purifying plant in district Swabi. The ethnobotanical information demonstrated in this study to be useful for a high level of diversity of medicinal plants. The study disclosed the popular knowledge of medicinal plants and their use for blood purification which is still alive in the study area. New medicinal plants reported will provide new research topics for chemical and activity studies.